2012
DOI: 10.1001/archopthalmol.2011.1378
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Retinal Tear Formation and Postoperative Rhegmatogenous Retinal Detachment in Transconjunctival Cannulated Vitrectomy Systems Compared With the Standard 20-Gauge System

Abstract: Objective: To compare 20-gauge standard pars plana vitrectomy (PPV) with transconjunctival cannulated PPV in the development of intraoperative retinal breaks and postoperative rhegmatogenous retinal detachments (RRDs) in a large series of patients undergoing PPV for macular pucker or macular hole. tation for pars plana vitrectomy (PPV) for macular pucker and macular hole continue to evolve. The latest advances include small-gauge, transconjunctival, cannulated systems; the first report on these systems was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…Similar to our study, other authors have also found a protective effect of microcannulas, especially when posterior vitreous detachment was induced during surgery [3,4,5,7]. However, in contrast to these other authors, we did not find any influence of the diagnosis on the rate of intraoperative retinal break formation [5,7]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to our study, other authors have also found a protective effect of microcannulas, especially when posterior vitreous detachment was induced during surgery [3,4,5,7]. However, in contrast to these other authors, we did not find any influence of the diagnosis on the rate of intraoperative retinal break formation [5,7]. …”
Section: Discussionsupporting
confidence: 82%
“…The issue of compromised wound integrity due to the lack of sutures possibly leading to complications such as hypotony, endophthalmitis and choroidal hemorrhage has been a matter of discussion [1]. However, one other important difference between the sutureless and the conventional techniques are the microcannula-guided entry sites into the eye [2,3,4,5,6,7]. Even though vitreous incarceration to the microcannulas has been documented, the microcannula system has been proposed to lower the risk of retinal dragging (with formation of iatrogenic retinal defects) during vitrectomy [3,4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, those who had used the system, including myself, attest to the fact that entry site tears were rare. Similarly, Covert et al reported intraoperative retinal breaks in a series of TSV (with cannula) and found that the incidence to be similar between 20-, 23-and 25-gauge (being 1 in 59 eyes, 3 in 76 and 3 in 76 cases respectively) [4].…”
mentioning
confidence: 85%
“…Nevertheless, those who had used the system, including myself, attest to the fact that entry site tears were rare. Similarly, Covert et al reported intraoperative retinal breaks in a series of TSV (with cannula) and found that the incidence to be similar between 20-, 23-and 25-gauge (being 1 in 59 eyes, 3 in 76 and 3 in 76 cases respectively) [4].Why should the use of a cannula system be associated with a lower incidence of entry site tears? It is speculated that the cannula protects the vitreous base from the trauma of repeated insertion of instruments, especially those with awkward shapes (such as scissors and forceps).…”
mentioning
confidence: 99%
“…Also they did not find any statistical difference in the incidence of retinal breaks between the two groups, which is in contrast to some major studies showing that the incidence of retinal breaks is significantly less in transconjunctival sutureless vitrectomy as compared with 20-gauge procedures. [34][35] In a large study, Jalil et al 36 have shown that the incidence of total anterior iatrogenic breaks was 16.7% for 20-G PPV and 7.8% for 23-G PPV, the difference being highly statistically significant.…”
Section: Non-observational Treatmentmentioning
confidence: 97%